2013
DOI: 10.1021/pr4008927
|View full text |Cite
|
Sign up to set email alerts
|

Using Proteomic Strategies for Sequencing and Post-Translational Modifications Assignment of Antigen-5, a Major Allergen from the Venom of the Social Wasp Polybia paulista

Abstract: Antigen-5 is one of the major allergens identified in wasp venoms, and despite the fact that its biological function is still unknown, many studies have demonstrated its allergenicity. In this study, the biochemical and structural characterization of antigen-5 from the venom of the social wasp Polybia paulista are reported. A gel-based mass spectrometry strategy with CID fragmentation methods and classical protocols of protein chemistry, which included N- and C-terminal sequencing, were used to assign the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…Moreover, cross-reactive carbohydrate determinants have been reported to induce carbohydrate-specific IgE antibodies [81,82,83]. Some studies have experimentally identified glycosylation sites in natural allergens as well as in recombinant allergens, highlighting their importance for IgE binding and for their recognition by innate immune cells [82,84,85,86]. For Blomia allergens, on the other hand, data on glycosylation have been mostly restricted to bioinformatics predictions [29,30,62,67,70,74].…”
Section: Posttranslational Modifications Of B Tropicalis Allergensmentioning
confidence: 99%
“…Moreover, cross-reactive carbohydrate determinants have been reported to induce carbohydrate-specific IgE antibodies [81,82,83]. Some studies have experimentally identified glycosylation sites in natural allergens as well as in recombinant allergens, highlighting their importance for IgE binding and for their recognition by innate immune cells [82,84,85,86]. For Blomia allergens, on the other hand, data on glycosylation have been mostly restricted to bioinformatics predictions [29,30,62,67,70,74].…”
Section: Posttranslational Modifications Of B Tropicalis Allergensmentioning
confidence: 99%
“…The antigens 5 are the most abundant proteins and most potent allergens in vespid venoms . These proteins of unknown function were found in the venoms of nearly all Vespoidea species, for example, social wasps of the Polistes, Dolichovespula, Vespa, Vespula and Polybia genera and show a varying degree of sequence homology.…”
mentioning
confidence: 99%
“…However, we observed loss of recombinant protein during long periods of culture (>48 h), possibly due to degradation by yeast proteases [25]. Native antigen 5 is known to be modified posttranslationally, including hydroxylation, phosphorylation and glycosylation [26]. The effect of these modifications on IgE reactivity should be further investigated.…”
Section: Discussionmentioning
confidence: 99%